(untitled) (Ágora de Heterodoxias, 2016)
The purpose of this paper is to establish a casual relation between service quality and its effect and impact in the loyalty and client’s satisfaction in the low-cost airlines in the State of Sonora. Service quality is measured through Cronin & Taylor (1994) ServPerf methodology, using the structural equation modeling (PLS-SEM). The analysis is based on 381 surveys randomly applied to the passengers of the three low-cost airlines operating in the state. The results showed that the passenger loyalty is explained in a 72.3% by the observable variable: satisfaction, followed by the endogenous latent variables: responsibility and empathy; while the variability in passenger’s satisfaction is explained in a 60.7% by the tangible elements, assurance and empathy. The information obtained from the data is important for the low-cost airlines in order to decide the quality dimensions they should focus to attract and retain a higher number of passengers, since a satisfied client will generate a strong identity with the airline brand, and therefore, a higher financial income and more clients for the company.